A stability-indicating UPLC method for the determination of curcumin diethyl disuccinate, an ester prodrug of curcumin, in raw materials. Issue 8 (August 2020) - Ratnatilaka Na Bhuket, Pahweenvaj; Wichitnithad, Wisut; Sudtanon, Orawan; Rojsitthisak, Pornchai
Abstract: A stability-indicating reversed-phase ultra-performance liquid chromatographic (UPLC) method for quantitative analysis of curcumin diethyl disuccinate (CDD) in raw materials was developed for applications in product development and quality control. Chromatographic separation was performed using the Waters ACQUITY UPLC® H-Class system consisting of an ACQUITY UPLC® BEH C18 (1.7 μm, 2.1 × 50 mm) column and a photodiode array detector set at a wavelength of 400 nm. The mobile phase consisting of 2%v/v acetic acid in water and acetonitrile was delivered at a flow rate of 0.3 mL/min under gradient elution program. The method was validated according to the ICH Q2(R1) guideline for the validation of analytical procedures. The method was found to be linear over the concentration range of 8–12 μg/mL with the coefficient of determination >0.995. The accuracy of the method established as %recovery ranged from 98.3 – 100.8%. The precision of the method expressed as %CV was found to be <1%. The coelution of degradation products from six stress test conditions was not observed. The method was robust under the variation of chromatographic parameters. The method was successfully applied in the determination of CDD content in raw materials. Abstract : Curcumin diethyl disuccinate; Stability-indicating method; UPLC; Validation; Prodrug; Analytical chemistry; Optical spectroscopy; Chromatography; Pharmaceutical chemistry; Pharmaceutical science.